Problematika Santri Dalam Pembelajaran Bahasa Arab di Pondok Pesantren An Nasyiin Pamekasan - Zahriyah, Sofiatus (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
In language learning for beginners will definitely find various kinds of problems, especially in learning foreign languages. This study aims to determine the problems contained in Arabic language learning both from linguistic problems and non-linguistic problems. The formulation of the problem in this study includes: 1) what are the linguistic and non-linguistic problems experienced by students of An nasyiin Islamic boarding school? how to solve the problem of learning Arabic students at the An Nasyiin Islamic boarding school? This research uses qualitative research methods and descriptive research , namely the data collected is in the form of words, images, and not numbers. This is due to the application of qualitative methods. In addition, everything collected is likely to be the key to what has been researched. The results of research on problems in Arabic learning include: language problems, namely problems in terms of sound, vocabulary, Qawā'id and Tarākib. And non-linguistic issues, including elements of student motivation, infrastructure, teacher competence, which of course have different social conditions and learning methods used during the Arabic learning process. And to overcome this problem, Students must learn more about the material that has been learned, and do a lot of discussions with friends who better understand Arabic learning material.